Multifactorial discrimination, discrimination salience, and prevalent experiences of internalized homophobia in middle-aged and older MSM - Meanley, Steven P. (Aging Ment Health, 2019)
OBJECTIVES: We sought to test whether discrimination salience and multifactorial discrimination were associated with prevalent experiences of internalized homophobia among middle-aged and older men who have sex with men (MSM). METHODS: We analyzed data from 498 middle-aged and older MSM from the Multicenter AIDS Cohort Study (MACS) who reported any lifetime discrimination experience. We estimated the prevalence ratio of current internalized homophobia using multivariable Poisson regressions, accounting for discrimination salience, multifactorial discrimination, and covariates. We then assessed whether multifactorial discrimination moderated the association between discrimination salience and internalized homophobia. RESULTS: Over half (56.4%) of our sample reported any current experience of internalized homophobia. More than two-thirds reported multifactorial discrimination (68.2%) and more than one-third (36.7%) reported moderate-to-high discrimination salience. Increases in discrimination salience (PR = 1.11; 95% CI: 1.03-1.20) were associated with any current internalized homophobia among middle-aged and older MSM. Multifactorial discrimination was not statistically associated with internalized homophobia and did not moderate the association between discrimination salience and internalized homophobia. CONCLUSIONS: Our study underscores internalized homophobia as a persisting concern among MSM in midlife and older adulthood. Our findings suggest that salience, as a characteristic of discrimination experiences, may have a greater impact on internalized homophobia compared with exposure. Future research efforts should assess facets of discrimination salience, such as severity, frequency, and chronicity, to better understand how discrimination shapes psychosocial well-being across the life course. Mental health advocates at policy, organizational, and community levels should aim to reduce intersectional stigma and address individual experiences of internalized homophobia.